The Criminal Responsibility of Offenders in the Trafficking of Protected Live Wildlife (A Case Study of Court Decision No. 674/Pid.B/LH/2024/PN Tjk) - Perdany, Aditya Rahmanda; Jainah, Zainab Ompu (The Future of Education Journal, 2025)
The illegal trade of protected wildlife remains a serious crime that threatens the sustainability of biodiversity in Indonesia. This study aims to analyze the factors that cause the crime of trading protected live wildlife and to examine the criminal liability of the perpetrators based on Verdict Number 674/Pid.B/LH/2024/PN Tjk. This research applies a normative juridical method with an empirical approach through literature studies, statutory regulations, and interviews. The findings reveal that economic motives are the dominant factor driving perpetrators to commit this crime, in addition to high market demand and weak law enforcement. The court decision shows that criminal liability has been applied in accordance with Article 21 paragraph (2) letter a in conjunction with Article 40 paragraph (2) of Indonesian Law Number 5 of 1990 concerning Conservation of Living Natural Resources and Their Ecosystems. The imposition of criminal sanctions in this verdict is deemed appropriate as an effort to suppress illegal practices and protect endangered species.